2012
DOI: 10.1111/j.1751-7893.2011.00336.x
|View full text |Cite
|
Sign up to set email alerts
|

Can a targeted psychological intervention be effective for young people following a first manic episode? Results from an 18‐month pilot study

Abstract: This study suggests that a manualized psychological intervention targeted to a first-episode population can be effective in reducing depression and overall symptom severity, and can improve functional outcome following a first episode of psychotic mania.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 54 publications
0
43
0
Order By: Relevance
“…Psychoeducation and cognitive-behavioural therapy (CBT) have been shown to be effective in BPD particularly if undertaken early in the course of the illness (Scott et al 2006;Colom, 2008;Macneil et al 2012) and in young people (Pavuluri et al 2004). Adding CBT to medication is associated with fewer relapses and cost savings of £1400 per patient (Lam et al 2008).…”
Section: Psychological Interventionsmentioning
confidence: 98%
“…Psychoeducation and cognitive-behavioural therapy (CBT) have been shown to be effective in BPD particularly if undertaken early in the course of the illness (Scott et al 2006;Colom, 2008;Macneil et al 2012) and in young people (Pavuluri et al 2004). Adding CBT to medication is associated with fewer relapses and cost savings of £1400 per patient (Lam et al 2008).…”
Section: Psychological Interventionsmentioning
confidence: 98%
“…39,40 For example, IPSRT showed a strong trend in improving the sleep profile of young adults, but showed no significant benefits for mood disorders (eg, three patients met depression criteria at baseline and four patients met depression criteria at follow-up). 37 CBT showed only weak effects on manic symptoms.…”
Section: Overview Of Outcomesmentioning
confidence: 99%
“…Five studies have been reported in individuals with first episode bipolar disorder: four case series 39,4143 and one clinical controlled trial (CCT) 40 . In two studies, 39,41 CBT was provided in adult mental health settings, whereas in the other three studies, 40,42,43 CBT was given as an early intervention in psychosis settings.…”
Section: Overview Of Outcomesmentioning
confidence: 99%
See 2 more Smart Citations